Molecular characterization and phylogenetic analysis of laccase producing fungal isolates with dye decolourizing potential - Gnanasalomi, V, Daphne Vivienne; Gnanadoss, J. Joel (Research in Biotechnology, 2013)
Twenty six fungi were isolated and screened for their ability to produce laccase on solid medium containing guaiacol and ABTS. Among these, six isolates showed positive laccase activity. They were quantitatively screened and the best two cultures were selected for further investigation. The two cultures also exhibited good dye decolorization ability. Molecular characterization based on the ITS rDNA region were carried out for the two cultures. The strains were identified as Psathyrella candolleana LCJ 178 and Myrothecium gramineum (GenBank accession numbers KF414680 and KF414681) respectively. These cultures showed the highest laccase production under submerged fermentation. This paper for the first time reports the production of laccase using Myrothecium gramineum and its ability to degrade dyes.